Patients’ Comprehension and Satisfaction With MRI and CT Scan Result Communication at Teaching Hospitals in Anambra State, Nigeria - Onwuka, Ifeyinwa Stella; Agbanu, V. N. (Darul Yasin Al Sys, 2025)
Effective communication of diagnostic results, particularly Magnetic Resonance Imaging (MRI) and Computed Tomography (CT) scans, is essential for improving patient comprehension, satisfaction, and overall healthcare outcomes. This study assessed patients’ understanding and satisfaction with the communication of MRI and CT scan results at two teaching hospitals in Anambra State, Nigeria: Nnamdi Azikiwe University Teaching Hospital (NAUTH) and Chukwuemeka Odumegwu Ojukwu University Teaching Hospital (COOUTH). A mixed-methods design was employed, combining quantitative surveys administered to 387 outpatients with qualitative interviews conducted with six medical doctors. Results indicated that patients generally exhibited a moderate level of comprehension and satisfaction with the communication process. Key barriers identified included time constraints, limited health literacy, language differences, emotional responses, and scan-related anxiety. Thematic analysis of physicians' perspectives revealed systemic and institutional challenges impacting communication efficacy. The study concludes that the delivery of diagnostic results extends beyond technical explanation and must be approached as a relational practice requiring clarity, empathy, and sufficient time. Recommendations include the integration of patient-centred communication training for healthcare professionals, the use of interpreters and visual aids, reorganization of physician workloads, and the implementation of structured feedback mechanisms. These strategies are vital for improving diagnostic communication practices and enhancing patient-centered care in resource-limited hospital settings.